2021
DOI: 10.1186/s13027-021-00375-2
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination strategy and anti - SARS-CoV-2 S titers in healthcare workers of the INT – IRCCS “Fondazione Pascale” Cancer Center (Naples, Italy)

Abstract: Background Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) infection and the resulting disease, coronavirus disease 2019 (COVID-19), have spread to millions of people globally, requiring the development of billions of different vaccine doses. The SARS-CoV-2 spike mRNA vaccine (named BNT162b2/Pfizer), authorized by the FDA, has shown high efficacy in preventing SARS-CoV-2 infection after administration of two doses in individuals 16 years of age and older. In the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 13 publications
6
19
0
Order By: Relevance
“…While high immunogenicity in MM patients is promising, clinical trials in the general population reported a 100% seroconversion rate for both vaccine types [ 3 , 4 ]. Median antibody titers in immunocompetent populations in response to the vaccine measured by the same assay used in this study have been found to be > 250 U/mL [ 13 , 14 ]. Of note, the only participant on teclistamab did not develop an antibody response.…”
Section: Discussionmentioning
confidence: 99%
“…While high immunogenicity in MM patients is promising, clinical trials in the general population reported a 100% seroconversion rate for both vaccine types [ 3 , 4 ]. Median antibody titers in immunocompetent populations in response to the vaccine measured by the same assay used in this study have been found to be > 250 U/mL [ 13 , 14 ]. Of note, the only participant on teclistamab did not develop an antibody response.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these analyzers are already present in many clinics and hospitals worldwide for diagnostic tests. The Roche Elecsys anti-SARS-CoV-2 S assay was also demonstrated to be a reliable assay to confirm recent COVID infections [26] and was proposed as a useful tool to evaluate the need for one or two vaccine doses in the case of pre-existing anti-SARS-CoV-2 antibodies, the purpose being to limit potential adverse effects [27]. Higher titers are indeed detected in people with a previous SARS-CoV-2 infection and also those who have been vaccinated compared to people without previous exposure to the virus: a median value of 30,527 U/mL in plasma for recovered COVID-19 patients versus a median value of 1975 U/mL in COVID-19 negative people 10 days post-vaccination [8].…”
Section: Discussionmentioning
confidence: 99%
“…On 22 nd December 2020, the Italian regulatory agency for drugs AIFA (Agenzia Italiana del Farmaco) authorized in Italy the use of BNT162b2/P zer vaccine, in 2 doses with an interval of 21 days between the doses [10]. Recent studies have found that subjects infected with COVID-19 develop higher antibody titers after vaccination [11] and present protective immunity for at least 6 months [12], but the impact of previous exposure to SARS-CoV-2 on immune response elicited by the vaccines needs to be further veri ed in larger trial studies. Several studies have shown that the immune response to the vaccine after the rst dose is substantially more pronounced in individuals with pre-existing immunity and it is similar to the immune response developed after the second dose in individuals not previously infected [11,13,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have found that subjects infected with COVID-19 develop higher antibody titers after vaccination [11] and present protective immunity for at least 6 months [12], but the impact of previous exposure to SARS-CoV-2 on immune response elicited by the vaccines needs to be further veri ed in larger trial studies. Several studies have shown that the immune response to the vaccine after the rst dose is substantially more pronounced in individuals with pre-existing immunity and it is similar to the immune response developed after the second dose in individuals not previously infected [11,13,14,15]. However, few data are available on the accurate monitoring of the titers' decline, response to further boosters, optimal vaccine dosage and role of different adjuvants on vaccine e cacy.…”
Section: Introductionmentioning
confidence: 99%